INVESTIGATING TYPES OF SENTENCES ON SHORT STORIES FROM THE STORY WEAVER WEBSITE - Azkiyyah, Hany Nur; Purnamasari, Yessy (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2023)
Most English students are still confused about the types of sentences and how to identify them. Also, most English students are not aware of the types of sentences. This study identifies what types of sentences are found in some short stories on the Story Weaver website and what type of sentence is mostly used. The qualitative method is applied, and a simple calculation is used to identify the frequency of each type of sentence. There are 12 stories with different levels based on most read by people. The data taken from the Story Weaver website and divided into four short stories with levels 1, 2, 3, and 4 based on the sorts of sentences: simple sentence, compound sentence, complex sentence, and compound-complex sentence. The data is selected by the most read people for each level. The data referring to sentences were identified and selected based on their types. The sentences were analyzed by their structure and types sentences based on the theory of Loberger and Shoup (2009). The result shows that the stories consist of 563 sentences. There are 374 of simple sentences, 35 compound sentences, 137 complex sentences, and 17 compound-complex sentences. From the result, it can be concluded that the most used type of sentence is simple sentence. The reason underlying the finding is that a simple sentence is suitable for beginners with easy words to help the reader quickly grasp the main point being made. Also, they convey a clear idea concisely and straightforwardly. In addition, simple sentences are commonly used because they are easier to read and understand, particularly for non-native speakers or those with limited language skills.